干预代谢危险因素对脑血管病影响的研究进展 - 张方圆, 薛婧, 许杰, 王拥军 ZHANG Fangyuan, XUE Jing, XU Jie, WANG Yongjun (Zhongguo cuzhong zazhi, 2024)
代谢危险因素是脑血管病的重要影响因素。随着代谢性脑血管病概念的提出，如何通过干预代谢危险因素改善此类患者的预后是未来重要的研究方向。代谢危险因素可相互影响并协同作用，降压、调脂、控制血糖等对传统代谢危险因素的干预可有效降低脑血管病的发病率和复发率；抗炎、补充维生素、调节肠道菌群等对残余代谢危险因素的干预同样是影响脑血管病发病及预后的重要措施。新型代谢药物“一专多能”的特点为代谢性脑血管病的治疗和管理提供了新的思路。本综述总结干预代谢危险因素对脑血管病影响的循证医学证据，旨在为代谢性脑血管病的管理提供更多理论支持。 Abstract: Metabolic risk factors play a significant role in the development of cerebrovascular diseases. With the concept of cerebro-metabolic disease proposed, how to improve the prognosis of patients with cerebro-metabolic disease by intervening metabolic risk factors is an important research direction in the future. Metabolic risk factors can interact and act synergistically. Intervention measures for traditional metabolic risk factors such as blood pressure lowering, lipid regulating, and blood glucose controlling can effectively reduce the incidence and recurrence rate of cerebrovascular diseases. Intervention measures for residual metabolic risk factors such as anti-inflammation, vitamin supplements, and regulation of intestinal flora are also key to affecting the incidence and prognosis of cerebrovascular diseases. The characteristics of new metabolic drugs with “one specialization and multiple capabilities” provide new ideas for the treatment and management of cerebro-metabolic disease. This review aims to provide more theoretical support for the management of cerebro-metabolic disease by summarizing evidence from evidence-based medicine on the influence of intervening metabolic risk factors on cerebrovascular diseases.